Fulfilment of Gender Needs in HIV and AIDS Control Programs: A Case Study of Housewives in Surakarta, Indonesia - Tiyas Nur Haryani; Ismi Dwi Astuti Nurhaeni; Argyo Demartoto (Jurnal Perempuan, 2017)
Since 2011, the number of case of HIV and AIDS suffered by Indonesian women tends to increase. However, the prevention of HIV and AIDS in Indonesia focuses only on high-risk group. Besides that, measures are not differentiated base on different needs of targetedgroup of programs. The article discusses gender mainstreaming in the prevention of HIV and AIDS program in Surakarta as well as the fulfilment of gender need of housewife who is prone to HIV and AIDS infection. The article is the result of a qualitative study with interactive analysis method. The research targeted housewives as research subjects due to the increasing number of housewives who suffer from HIV and AIDS infection. Moreover, they even placed as the second highest group infected by the disease in Surakarta. The data was collected from an in-depth interview, documentation and observation. The finding showed that the quality of gender equality in the HIV and AIDS mitigation policy in Surakarta is positioned in a gender neutral level, providing the equal rights and obligations for all citizens, regardless of their sex. This matter gives impact to the prevention of HIV and AIDS program that only focuses on the fulfilment of housewives practical gender needs.